Rethinking international research partnerships for just and equitable futures - Gyamerah, Kenneth (Journal of International Students, 2026)
International research partnerships are mostly promoted by universities, funding agencies, and international development organizations as pathways for capacity building and global knowledge exchange. In practice, however, some partnerships reproduce coloniality in research through Northern‐led agenda setting, extractive data collection in the Global South, inequitable authorship practices, and asymmetric control over funding. This article examines how mainstream research partnership models position researchers, institutions and communities in the Global South primarily as data providers, while epistemic authority, publication credit, and research capital remain concentrated in Global North institutions. Drawing on Ubuntu relationality, I advance an anticolonial framework for rethinking international research partnerships toward just futures. Ubuntu relationality challenges coloniality in research by foregrounding relational accountability, reciprocity, shared governance, and collective ethical responsibility across institutions, researchers, and communities. The article also introduces a guide to support researchers in operationalizing Ubuntu’s communal principles in the design, governance, and evaluation of international research partnerships.